No more tears without tiers? The impact of indirect settlement on liquidity use in TARGET2 - Jan Paulick; Ron Berndsen; Martin Diehl; Ronald Heijmans (Empirica, 2023)
We study the impact of tiered payments originating from client banks on the liquidity consumption (relative intraday liquidity use) of settlement banks. Estimates of a panel data model, employing wholesale payments in euro, show that a higher share of tiered payments reduces liquidity consumption by settlement banks. Metrics on timing, delay, and payment priorities suggest that settlement banks use more leeway in settling tiered payments from client banks compared to in-house payments. Payment timing as a proxy for external delay suggests that tiered payments help smooth liquidity positions. Payment delay within the system does not follow a clear dynamic over time, whereas banks consistently de-prioritize tiered payments. Thereby, settlement banks employ tiered arrangements to manage intraday liquidity more efficiently. To a certain extent, this hints at "free riding" or higher recycling of liquidity from client banks' payments. However, the results are also consistent with settlement banks' monitoring role or tiered payments potentially exhibiting different characteristics which may be attributable to contractual arrangements.
Keywords: E42; E58; G21; 330; RTGS systems; Banks; Payments; Tiering; Liquidity; TARGET2